Lexical innovation processes of youth netspeak on Malay twitter posts - Nur Nashatul Nasuha Nazman,; Su-Hie Ting,; Kee-Man Chuah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The formation of neologisms in Malay has not been extensively studied and therefore has yet to be fully understood. The current study examined the lexical innovation processes in Twitter posts in Malay. A 25,679-word corpus was compiled from 2,000 tweets of 200 Malaysian Twitter users in their twenties. The textual analysis performed through AntConc software identified “ni” (this) and “nk” (want) as the top two neologisms, and these words constituted 45.8% of the corpus. Most of the neologisms are formed through clipping (65%) and pseudo-elliptical construction (26%), while blending (7%) and elongation (2%) are minor word formation processes. The clipping affects vowels (28%) more than consonants (9%), whether it is deletion, replacement, or addition. The pseudo-elliptical constructions involve letters of the alphabet and phonological adjustments to vowels and consonants. On vowel changes, the results show that there is a simplification of diphthongs to monophthongs, and a movement towards vowels in the middle position [e] or [o]. As for consonant changes, there is a shift in the place of articulation towards bilabial consonants [p], [m], and [w] and words containing [h] and [r] are likely to be dropped or replaced. The changes in the spelling are a result of changes in the spoken discourse. The findings suggest that exploring the phonological rules can explain pseudo-elliptical constructions, leading to a better framework on morphology and phonology to understand formation of neologisms in social media discourse.